3D printing and shaping polymers, composites, and nanocomposites: a review - M. Azlin, M. N.; Ilyas, R. A.; M. Zuhri, M. Y.; M. Sapuan, S.; M. Harussani, M.; Sharma, Shubham; Nordin, A. H.; M. Nurazzi, N.; Afiqah, A. N. (Multidisciplinary Digital Publishing Institute, 2022)
Sustainable technologies are vital due to the efforts of researchers and investors who have allocated significant amounts of money and time to their development. Nowadays, 3D printing has been accepted by the main industry players, since its first establishment almost 30 years ago. It is obvious that almost every industry is related to technology, which proves that technology has a bright future. Many studies have shown that technologies have changed the methods for developing particular products. Three-dimensional printing has evolved tremendously, and currently, many new types of 3D printing machines have been introduced. In this paper, we describe the historical development of 3D printing technology including its process, types of printing, and applications on polymer materials.